Interpretation of Incest According To the Mazhab Syafi`I and the Laws of Brunei Darussalam - Roslan, Fatin Nuraliah Syazwani; Mahmud, Dr. Hafini (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Incest (Sumbang Mahram) refers to a sexual relationship between two individuals who are prohibited from marrying under Sharia law. If left unaddressed, incest can negatively impact the honor and integrity of a family, potentially leading to the severance of familial bonds known as qatl al-arham which may result in disputes and a loss of trust among family members. This raises the question of how incest is interpreted within mazhab Syafi'i and under the laws of Brunei Darussalam. This analytical study aims to provide a deeper understanding by exploring the differing perspectives of the Syafi'i jurisprudence and Brunei Darussalam's legal framework. To achieve this, the research employs a qualitative approach, specifically a library-based study, utilizing both classical and contemporary fiqh texts and relevant legislation such as the Religious Council and Kadi Courts Act, chapter 77, Brunei Penal Code chapter 22, and the Syariah Criminal Code Order, 2013. These sources are used to examine views on incest. A comparative analysis will be conducted between mazhab Syafi`i and the legislative provisions for both Syariah and Civil laws across various aspects. The study is expected to conclude that, according of mazhab Syafi'i, incest is classified as zinā. In contrast, under Brunei law, incest is described as a man and a woman having sexual intercourse who share a close familial relationship and are prohibited from marrying according to Islamic law. Keywords: Sumbang Mahram, Incest, Zina, Mazhab Syafi`i, Brunei Darussalam Law